Invasive freshwater snails form novel microbial relationships. (20th November 2020) - Bankers, Laura; Dahan, Dylan; Neiman, Maurine; Adrian‐Tucci, Claire; Frost, Crystal; Hurst, Gregory D. D.; King, Kayla C.
Abstract: Resident microbes (microbiota) can shape host organismal function and adaptation in the face of environmental change. Invasion of new habitats exposes hosts to novel selection pressures, but little is known about the impact on microbiota and the host–microbiome relationship (e.g., how rapidly new microbial associations are formed, whether microbes influence invasion success). We used high‐throughput 16S rRNA sequencing of New Zealand (native) and European (invasive) populations of the freshwater snail Potamopyrgus antipodarum and found that while invaders do carry over some core microbial taxa from New Zealand, their microbial community is largely distinct. This finding highlights that invasions can result in the formation of novel host–microbiome relationships. We further show that the native microbiome is composed of fewer core microbes than the microbiome of invasive snails, suggesting that the microbiota is streamlined to a narrower set of core members. Furthermore, native snails exhibit relatively low alpha diversity but high inter‐individual variation, whereas invasive snails have higher alpha diversity but are relatively similar to each other. Together, our findings demonstrate that microbiota comparisons across native and invasive populations can reveal the impact of a long coevolutionary history and specialization of microbes in the native host range, as well as new associations occurring after invasion. We lay essential groundwork for understanding how microbial relationships affect invasion success and how microbes may be utilized in the control of invasive hosts.